EXAMINING SPEAKING ANXIETY OF INTERNATIONAL RELATIONS STUDENTS IN INDONESIAN UNIVERSITY - Syifa, Fayza As; Khatimah, Khusnul (English Language Teaching Methodology, 2024)
This study delves into the examination of English speaking anxiety levels among students enrolled in the International Relations Program at Universitas Muhammadiyah Kalimantan Timur. Its primary objective is to discern the extent of anxiety experienced by students, identify the factors influencing it, and explore effective strategies to overcome this prevalent issue. Through the utilization of the Foreign Language Speaking Anxiety Scale (FLSAS) developed by Balemir (2009), coupled with comprehensive in-depth interviews, the research findings indicate that a significant majority, accounting for 65% of students, grapple with moderate levels of speaking anxiety. The average scores derived from the assessment of different dimensions of anxiety reveal notable figures: 3.26 for Communication Anxiety, 3.16 for Test Anxiety, and 3.26 for Fear of Negative Evaluation. The principal contributing factors exacerbating anxiety include communication apprehension, test-related anxiety, and fear of negative evaluation, often stemming from inherent uncertainties surrounding language proficiency and apprehensions regarding comprehension abilities. Effective coping mechanisms identified to alleviate this pervasive anxiety encompass a multifaceted approach, including practices such as speaking exercises in front of a mirror, meticulous preparation of speaking material, and consistent engagement in repeated practice sessions. These strategies collectively contribute to bolstering confidence levels while concurrently mitigating anxiety symptoms. This comprehensive study not only lays a robust foundation for tailored interventions aimed at ameliorating English communication skills among students but also sheds light on the intricate interplay between anxiety levels, underlying factors, and the efficacy of coping strategies.